Phylogenetic Diversity and Dispersion of Ants Worldwide: Geographic Variation and Climatic Correlates - Hong Qian; Runxi Wang; Michael Kessler; Shenhua Qian; Jamie M. Kass; Evan P. Economo; Benoit Guénard (Global Ecology and Biogeography, 2026)
Aim Species composition in biological assemblages is driven by an interplay of evolutionary, environmental, and ecological processes. Investigating the relationships between evolutionary history and climatic conditions can shed light on the variation in biodiversity and phylogenetic structure in biological assemblages. Harnessing a global dataset of ant biodiversity, here we determine the extent to which climate drives geographic patterns of phylogenetic diversity and dispersion in ants. Methods We calculated mean pairwise distance (MPD, measuring phylogenetic diversity) and the standardized effect size of MPD (MPD ses , measuring phylogenetic dispersion) in each of over 11,500 ant assemblages, and related them to variables representing current climatic conditions and Quaternary climate change. Location Global. Time Period Current. Taxon Ants. Results We find that these two metrics are positively correlated with climate averages yet negatively correlated with climate variability. We also find that current climatic conditions are more strongly associated with these phylogenetic metrics than Quaternary climate change. Temperature variables had stronger associations than precipitation variables, and climate extremes and seasonality affected phylogenetic diversity and dispersion equally. Lastly, areas with higher phylogenetic diversity and dispersion tend to have more paleo‐endemic lineages. Main Conclusions The geographic patterns and climatic associations with ant phylogenetic diversity and dispersion found in this study are largely consistent with those found in butterflies and several plant groups, suggesting that the same mechanisms may have driven phylogenetic structure more broadly across the tree of life.